One-pot synthesis of hierarchically structured ceramic monoliths with adjustable porosity - Drisko, Glenna L. (2010)
Hierarchically porous oxides are used in a variety of applications within the energy sector (e.g., fuel cells, batteries), biology (e.g., scaffolds, biocatalysis), separations, and catalysis. This article describes a reproducible one-step method for the preparation of metal oxides with controllable hierarchical pore architectures. The preparation is demonstrated for a wide range of materials, specifically silica, titania, zirconia, aluminum titanium oxide, titanium zirconium oxide, and yttrium zirconium oxide monoliths. The samples were prepared by exploiting the polymerization and phase separation of furfuryl alcohol to produce a colloidal dispersion of poly(furfuryl alcohol) particles. The gelation in the sol-gel process occurred after the in situ formation of the template. The removal of the polymer template led to the formation of macropores, whereas inclusion of an amphiphilic block copolymer (Pluronic F127) assisted mesopore formation, either by templating or by stabilizing the inorganic building blocks. The macropore and mesopore morphology could be altered by varying the synthesis conditions. This control over the pore structure was demonstrated in the silica, titania, and titanium zirconium oxide materials.